Analysis of Bachelor of Science in Nursing Education in Sierra Leone: A look at program fidelity and student satisfaction - Andrew Mclellan; Abdi Aden; Antoine Lacroix; Joan Shephard (Elsevier, 2020)
Program evaluations play an important role in nursing education. Program evaluation is an integral part of program planning and implementation by nursing faculties and administrators. Guided by the organizing framework of the WHO's Global Standards for the Initial Education of Professional Nurses and Midwives (2009) in combination with the Standards for Basic Nursing and Midwifery Education for Sierra Leone (2016) the study provides an objective description of the current status of Bachelor of Science in Nursing (BScN) education in Sierra Leone. By ascertaining the program fidelity and student satisfaction of BScN education in Sierra Leone the study highlights some of the strengths, challenges, and areas for improvement. The program evaluation may provide a roadmap for future nursing program evaluations, including diploma and certificate nursing programs, and may help focus future interventions in strengthening BScN education in Sierra Leone.